Chemistry teacher responses to learning in the COVID-19 outbreak: Challenges and opportunities to create innovative lab-work activities. Issue 1 (March 2021) - Shidiq, A S; Permanasari, A; Hernani,; Hendayana, S
Abstract: The COVID-19 pandemic has forced schools to make a shift in learning mode, from face to face become online remote learning. This is also faced and done by chemistry teachers. The study was conducted to investigate the response of chemistry teachers to online learning in the COVID-19 pandemic. A purposive survey method was used in this study by giving online questionnaires through Google form containing 10 open questions about chemistry learning and practicum conducted by the chemistry teachers in the COVID-19 pandemic. The data were collected for a week at the beginning of June 2020. A total of 55 chemistry teachers from West Java participated as respondents. The result found that chemistry teachers had tried to utilize various technology platforms in conducting learning. Moreover, most of them faced difficulty to arrange the lab-work activities and did nothing. Some teachers try to find lab-work multimedia instead of real activities. However, the multimedia commonly did not make students pertain the processes skills. Since the pandemic could not be predicted when it will finish, this is a kind of challenges and opportunities to think about implementing online chemistry learning from now and then.